1997
DOI: 10.1002/(sici)1098-2795(199710)48:2<208::aid-mrd8>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Transition from maternal to embryonic control of development in IVM/IVF domestic cat embryos

Abstract: The timing of the transition from maternal to zygotic control of development (MZT) and the initiation of transcription was studied in domestic cat embryos to determine if there is a temporal association between these phenomena and the developmental block observed in cat embryos fertilized in vitro. Embryos were derived from in vitro‐matured, in vitro‐fertilized (IVM/IVF) oocytes. In Experiment 1, embryos (n = 52) were cultured continuously in the presence of 10 μg/ml α‐amanitin (a transcriptional inhibitor) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
2
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 43 publications
(62 reference statements)
2
24
2
2
Order By: Relevance
“…In contrast to bovine oocytes, we found that porcine oocytes were able to support nucleoli formation in nuclei of many species: equine, rabbit, canine, and feline that possess very close EGA at the 4-to 8-cell stage (Grøndahl & Hyttel 1996, Hoffert et al 1997, Kanka 2003, Maddox-Hyttel et al 2005, and, interestingly, even in some ovine nuclei with EGA at the 8-cell stage (Crosby et al 1988). The most intensively nucleolinlabeled nucleoli were found in equine and rabbit nuclei.…”
Section: Discussioncontrasting
confidence: 61%
“…In contrast to bovine oocytes, we found that porcine oocytes were able to support nucleoli formation in nuclei of many species: equine, rabbit, canine, and feline that possess very close EGA at the 4-to 8-cell stage (Grøndahl & Hyttel 1996, Hoffert et al 1997, Kanka 2003, Maddox-Hyttel et al 2005, and, interestingly, even in some ovine nuclei with EGA at the 8-cell stage (Crosby et al 1988). The most intensively nucleolinlabeled nucleoli were found in equine and rabbit nuclei.…”
Section: Discussioncontrasting
confidence: 61%
“…However, an effect was expressed in a greater incidence of developmental arrest at <8 cells as well as reduced overall percentage of blastocysts and blastomeres per blastocyst. The developmental stage most sensitive to this initial hyperosmotic condition was near the 8-cell stage, an interval associated with activation of the embryonic genome (Hoffert et al, 1997). Exposures to osmolarities ≥1,000 mOsm impacted the embryo development first (50-80% decrease in the proportion of blastocysts) and then nuclear maturation (25% decrease in MII).…”
Section: Discussionmentioning
confidence: 99%
“…The timing of embryonic gene activation is species-specific (Manes, 1973;Camous et al, 1986;Braude et al, 1988;Crosby et al, 1988;Zernicka-Goetz, 1994;Hoffert et al, 1997). In mouse a major burst of zygotic gene expression occurs at the two-cell stage corresponding to the time at which mRNAs for the majority of maternal transcripts are degraded (Schultz, 1993).…”
Section: Introductionmentioning
confidence: 99%